BVOC-aerosol-climate interactions in the global aerosol-climate model ECHAM5.5-HAM2 - R. Makkonen; A. Asmi; V.-M. Kerminen; M. Boy; A. Arneth; A. Guenther; M. Kulmala (Atmospheric Chemistry and Physics, 2012)
The biosphere emits volatile organic compounds (BVOCs) which, after oxidation in the atmosphere, can partition on the existing aerosol population or even form new particles. The large quantities emitted provide means for a large potential impact on both aerosol direct and indirect effects. Biogenic responses to atmospheric temperature change can establish feedbacks even in rather short timescales. However, due to the complexity of organic aerosol partitioning, even the sign of these feedbacks is of large uncertainty. We use the global aerosol-climate model ECHAM5.5-HAM2 to explore the effect of BVOC emissions on new particle formation, clouds and climate. Two BVOC emission models, MEGAN2 and LPJ-GUESS, are used. MEGAN2 shows a 25% increase while LPJ-GUESS shows a slight decrease in global BVOC emission between years 2000 and 2100. The change of shortwave cloud forcing from year 1750 to 2000 ranges from −1.4 to −1.8 W m−2 with 5 different nucleation mechanisms. We show that the change in shortwave cloud forcing from the year 2000 to 2100 ranges from 1.0 to 1.5 W m−2. Although increasing future BVOC emissions provide 3–5% additional CCN, the effect on the cloud albedo change is modest. Due to simulated decreases in future cloud cover, the increased CCN concentrations from BVOCs can not provide significant additional cooling in the future.